hoe can we solve the quadratic equation - 12abx^2-(9a^2-8b^2)x-6ab=0

Asked by  | 2nd Oct, 2012, 07:58: PM

Expert Answer:

Answer : Given equation 12abx2-(9a2-8b2)x-6ab=0
The given equation is in the form of Ax2 +Bx +C =0
 
here A = 12 ab , B = -(9a2-8b2) , C = -6ab  
 
=> D2 = B2- 4 AC
     = (9a2-8b2)2 -4(12ab)(-6ab)
     = (9a2-8b2)2 + 288a2b2
     = 81 a+64b4 -144a2b2 + 288a2b2
     =81 a+64b4 +144a2b2 
 =>D2 = (9a2+8b2)2
=> D =(9a2+8b2) , - (9a2+8b2)
 
x = (-B +D) / 2A , (-B - D) / 2A
=> x =  (9a2-8b2+ 9a2+8b)/2(12ab) ,
(9a2-8b-9a2-8b)/2(12ab) 
=> x = 18 a/24ab , -16b2/24ab
=> x = 3a/4b , - 2b/3a Answer   
 

Answered by  | 2nd Oct, 2012, 10:52: PM

Queries asked on Sunday & after 7pm from Monday to Saturday will be answered after 12pm the next working day.